English – Indonesian Code Mixing of Fani Rahm Beauty Vlogs: Sociolinguistics Approach - Dinda Sekar Ayu Wulandari; Dwi Haryanti (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This research aims to identify the types of code-mixing used in Fani Rahm’s YouTube videos and to classify the factors influencing their use in her content. This study employs a qualitative descriptive approach to analyze code-mixing in Fani Rahm’s YouTube videos. The research data consists of utterances containing English code-mixing in Indonesian, obtained from three selected videos. Data collection techniques included observation, repeated viewings, and video transcription. The data were then analyzed by classifying code-mixing types according to Hoffman’s (1991) theory and identifying the social factors influencing code-mixing use according to Weinreich’s (1963) theory. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing, and its validity was tested through source triangulation. The result of this study is that English–Indonesian code-mixing in Fani Rahm’s YouTube beauty content appears in three forms: intra-sentential, intra-lexical, and pronunciation change. It is influenced by low-frequency words, audience design, and oversight, where English is used for precision, audience adaptation, and habitual exposure. Overall, code-mixing functions as a purposeful strategy to enhance clarity, engagement, and bilingual identity in digital beauty discourse.